2001
DOI: 10.1108/14601060110399306
|View full text |Cite
|
Sign up to set email alerts
|

Internet shopping adoption by Greek consumers

Abstract: This paper aims at developing profiles of consumers who have already conducted shopping through the Internet and of those who are interested to adopt Internet shopping as an innovation. Based on the theories and processes of consumer adoption decision and diffusion of innovations, the study measures demographic and behavioural characteristics, as well as perceptions and preferences of Greek consumers towards distance shopping in general and Internet retailing in particular. The survey conducted offers insightf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 8 publications
9
74
0
4
Order By: Relevance
“…Age is inversely related to e-shopping in a non-linear manner; people up to the age of 40 are inclined to buy online, while the probability of buying online decreases after that age (Vrechopoulos et al, 2001;Farag et al, 2003). Not surprisingly, individuals with a higher income and education shop online more often (Casas et al, 2001;Vrechopoulos et al, 2001;Sim and Koi, 2002). Other factors appear to be inconclusive.…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Age is inversely related to e-shopping in a non-linear manner; people up to the age of 40 are inclined to buy online, while the probability of buying online decreases after that age (Vrechopoulos et al, 2001;Farag et al, 2003). Not surprisingly, individuals with a higher income and education shop online more often (Casas et al, 2001;Vrechopoulos et al, 2001;Sim and Koi, 2002). Other factors appear to be inconclusive.…”
Section: Background Literaturementioning
confidence: 99%
“…Previous study has shown that in general, most online buyers are male; however, most online grocery shoppers are female (Casas et al, 2001;Vrechopoulos et al, 2001;Morganosky and Cude, 2000;Raijas, 2002;Farag et al, 2003). Age is inversely related to e-shopping in a non-linear manner; people up to the age of 40 are inclined to buy online, while the probability of buying online decreases after that age (Vrechopoulos et al, 2001;Farag et al, 2003). Not surprisingly, individuals with a higher income and education shop online more often (Casas et al, 2001;Vrechopoulos et al, 2001;Sim and Koi, 2002).…”
Section: Background Literaturementioning
confidence: 99%
“…Price Price of the product being an important factor affecting online buying behavior, prices of the web store should not be higher than those of the physical stores. There have been evidence by researchers where internet shoppers don't prefer to buy online if the prices are higher (Vrechopoulos et al, 2001). Customer seek abundant choice and low price from online stores (Khan et al, 2015).…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%
“…They compared users and the non-users of EGSs and found that consumers prefer an electronic channel over a traditional one because of lower price-level, better service and information. Vrechopoulos et al, (2001) suggested virtual retailers to offer personalized shopping environments according to their customers' specific needs and wishes because provision of a one-to-one instead of a one-to-many shopping experience constitutes a critical success factor. Another important factor is provision of alternative payment methods.…”
Section: Phase I (From 1997-2000)mentioning
confidence: 99%
“…In contrast, information for experience goods is rather complex and too costly to gather by modes other than direct experience (eg perishables, clothes, and shoes). These attributes of products not only have an impact on the choice for a searching mode but also on the choice for a channel (Farag, 2006;Hjorthol, 2009;Lee, 2002;Vrechopoulos et al, 2001). The choice for a delivery mode depends on the size, weight, and price of products, and on how perishable they are (Rotem-Mindali and Salomon, 2009).…”
Section: Decomposing Shoppingmentioning
confidence: 99%